Strategi Terapiutik Korban Homoseks: Studi Terhadap Pemikiran Ibnu Qayyim al-Jauziyah - Aswar Aswar; Mukran H. Usman; Azwar Iskandar (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2020)
This study aims to find the therapeutic strategies to the gay victims. The phenomenon of the rising of the gay community is increasingly worrying, of course that behavior is abnormal for Indonesians, especially for Muslims. This community actually began to grow in 1982 in Solo, 1985 in Yogyakarta, 1993 in Pekanbaru, 1999 in Surabaya, and still exists in cyberspace (social media). The research method applied is a qualitative approach with the type of composed hermeneutics research analysis, with the object study of therapeutic thought of Ibn Qayyim al-Jauziyah and the examined subject in the RSC-M Malang (Ruqyah Syar'iyyah Center Malang). The study found four therapeutic strategies that can be applied to the gay victims. First, the main focus of intervention is in mind/belief intervention. Second, the target towards an ideal person is the transfer from a sinful person to a person who obeys God's commandments and avoids His prohibition. Third, analysis and diagnosis is efforts to identify and find the errors in the chain of perception, belief, sex drive, behavior, and habit of the gay victims. Fourth, the application of homosexual victim alleviation techniques consists of prevention and healing pathways, prevention pathways is in the form of 'self-training' subjecting themselves to the same things, while healing pathways is in the form of the application of intervention techniques of the mind, self-conversion and statements of repentance and istigfar, as well as the worship therapy. The recommendations of this study is to be applied by practitioners and counsellors in providing counselling services to the gay victims.